Phenotypic Variation of Four Populations of Osyris lanceolata Hochst. & Steud. (African Sandalwood) in Kenya - Andiego, K. P.; Dangasuk, O. G.; Otieno, F. D.; Omondi, S. F.; Odee, W. D. (Africa Environmental Review Journal, 2022)
African sandalwood (Osyris lanceolata) is a dioecious and semi-parasitic tree at risk of extinction due to overexploitation for its essential oil, a product used in the perfumery and pharmaceutical industries. This study therefore determined the level of morphological variation in four kenyan populations of O. lanceolata, namely Gwasii, Kabarnet, Marigat, and Kitui, with the objective of recommending conservation strategies for the species. morphological traits were analysed using Anova and coefficient of variation. genetic similarity was analysed using a multivariate analysis using euclidean distance and a dendrogram constructed based on unweighted pair group method with arithmetic mean (UPGMA). Results showed that, Gwasii trees had significant higher diameter at breast height (dbh), crown diameter (crd), and flower diameter (fld) than the rest. female trees had greater growth and floral mean values than male trees as observed in tree height (het), dbh, crd, flower length (fll) and fld. Analysis based on euclidean distance clearly distinguished Gwasii population from the Kitui, Kabarnet, and Marigat populations, which individuals revealed genetic interrelationship. in conclusion, morphological traits revealed great individual interspersion within and among populations revealing population genetic interrelationships. Study recommended that Gwasii population should be prioritized for ex-situ conservation while in-situ conservation should target plus trees in entire populations.